2020
DOI: 10.1177/0036850420927249
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on mechanical properties of heavy-haul low-vibration track under train static load

Abstract: In this paper, a full-scale model of Low Vibration Track was established and three working conditions were applied to a single bearing block; these include: vertical load at the end of the track slab, combination of horizontal and vertical load at the end of the track slab, and vertical load at the middle of the track slab. By applying four times static wheel load to the full-scale model, the relationship between the stress of the track structure and the load under different working conditions was investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The corner of the sleeper is a bulge, which can easily cause strain concentration. It has been demonstrated that the strain here is in a large state [26]. In the test, measuring points 5 and 6 were not only located at the corner of the sleeper, but also at the outside of the self-compacting concrete cushion, which means that the bottom of points 5 and 6 was in the suspended state.…”
Section: Strain Of the Sleeper Slab Trackmentioning
confidence: 89%
“…The corner of the sleeper is a bulge, which can easily cause strain concentration. It has been demonstrated that the strain here is in a large state [26]. In the test, measuring points 5 and 6 were not only located at the corner of the sleeper, but also at the outside of the self-compacting concrete cushion, which means that the bottom of points 5 and 6 was in the suspended state.…”
Section: Strain Of the Sleeper Slab Trackmentioning
confidence: 89%
“…The main shortcomings are the following: the new and old concrete junction area is larger, crack control is more difficult; the weight of prefabricated sleepers is larger, compared with DBT, it is more difficult to transport, assemble and lay. (3) LVT The LVT structure (Figure 4) mainly includes concrete track bed slab, elastic support block (concrete support block, rubber boot cover, rubber pad under the block) and supporting fasteners [15]. LVT is composed of rubber or other elastic composite boots at the lower part and around the double-piece sleeper (or two independent support blocks).…”
Section: Introduction 1engineering Backgroundmentioning
confidence: 99%
“…The main disadvantages are the following: poor waterproof and dustproof performance of boots; durability of elastic elements in the structure; relatively weak retaining ability of track geometry. (3) LVT The LVT structure (Figure 4) mainly includes concrete track bed slab, elastic support block (concrete support block, rubber boot cover, rubber pad under the block) and supporting fasteners [15]. LVT is composed of rubber or other elastic composite boots at the lower part and around the double-piece sleeper (or two independent support blocks).…”
Section: Introduction 1engineering Backgroundmentioning
confidence: 99%
See 2 more Smart Citations